Penerapan Metode Cooperative Script Menggunakan Media Mind Mapping untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPS di MTsN 3 Kuningan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of implementing the Cooperative Script method using Mind Mapping media in improving students’ comprehension in Social Studies subjects at MTsN 3 Kuningan. The scope of the study focuses on ninth-grade students with a total sample of 30 participants. This research employed an experimental method with a pretest-posttest control group design. Data were collected through written tests administered before (pretest) and after (posttest) the learning method was applied. Data analysis was conducted using the t-test to examine differences in learning outcomes before and after treatment. The results showed a significant improvement in students’ comprehension, with the posttest mean score (80.00) being higher than the pretest mean score (50.00). The t-count value (2.382) was greater than the t-table value (2.042), with a significance level of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted. It can be concluded that the Cooperative Script method combined with Mind Mapping media is effective in enhancing students’ learning outcomes. The implications of this research suggest that teachers can utilize this method and media to create more active, creative, and motivating learning environments for better material comprehension.